Calculation of the Overall Coordination Internal Force of the Grille Beam-Column under the Impact of Debris Flow - Yongsheng Wang; Hao Zhu; Bing Wang (Advances in Materials Science and Engineering)
At present, the research on the new ground anchor counterfort grille dam is not perfect. In order to analyze and design the new grille dam accurately and reasonably, it is necessary to carry out theoretical research on the internal force calculation of the overall coordination of the grille beam-column under the impact of debris flow. Under the condition of full reservoir of debris flow, the grille beam-column meets the working principle of elastic foundation beam; therefore, the equation of the overall cooperative work of the grille beam-column is derived based upon Winkler’s theory of elastic foundation beam. Finally, combined with the engineering example, this calculation method is used for analysis; the results show that the bending moment of the grille beam-column increases compared with that regardless of considering the overall coordination, and the increased value of the bending moment at the bottom of the grille column and the middle of the grille beam is the largest. Therefore, from the perspective of safety, the overall coordination cannot be ignored when designing a blocking dam.